Observer-based H∞ control on nonhomogeneous discrete-time markov jump systems - Yin, Y.; Shi, P.; Liu, F.; Teo, Kok Lay (Silverchair information/systems, 2013)
This paper concerns the problem of observer-based H8 controller design for a class of discrete-time Markov jump systems with nonhomogeneous jump parameters. A nonhomogeneous jump transition probability matrix is described by a polytope set, in which values of vertices are given. By Lyapunov function approach, under the designed observer-based controller, a sufficient condition is presented to ensure the resulting closed-loop system is stochastically stable and a prescribed H8 performance is achieved. Finally, a simulation example is given to show the effectiveness of the developed techniques.